PENGARUH MEDIA PEMBELAJARAN E-LEARNING, GAYA BELAJAR, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SIMULASI DAN KOMUNIKASI DIGITAL KELAS X DI SMK NEGERI 2 PINRANG - Nur Syamsinar Munir; Hamsu Abdul Gani; Abdul Muis Mappalotteng (UNM Journal of Technology and Vocational, 2022)
The study aims to discover: 1) the influence of using E-Learning media on learning motivation; 2) the Influence of learning style on learning motivation; 3) the influence of learning motivation on learning outcomes; 4) the influence of the use of E-Learning media on learning outcomes both directly and through learning motivation; and 5) the influence of learning style on learning outcomes both directly and through learning motivation. The type of research used is a type of quantitative research with a path analysis model. The total population is 120 people. The sample size is 89 people obtained by employing random proportional technique. Data collection was conducted through documentation, questionnaires, and tests. The results of the study indicate that: (1) there is a significant influence the use of E-Learning media on learning motivation; (2) there is a significant influence learning style on learningmotivation; (3) there is a significant influence learning motivation on learning outcomes; (4) there is a significant influence the use of E-Learning Media on learning outcomes either directly or through learning motivation, and (5) there is a significant influence learning style on learning outcomes either directly or through learning motivation.